2021
DOI: 10.1111/pace.14328
|View full text |Cite
|
Sign up to set email alerts
|

Severity of spleep apnea syndrome and life‐threatening tachyarrhythmias in patients with implantable cardioverter defibrillator

Abstract: Background: Sleep apnea syndrome (SAS) has been reported to be associated with a higher incidence of ventricular arrhythmias. The aim of this study was twofold: (1) to investigate whether in SAS patients receiving an implantable cardioverter defibrillator (ICD) the severity of SAS was associated with the occurrence of ventricular arrhythmias; (2) to assess whether changes in nocturnal apnoic/hypopnoic episodes may favor the occurrence of life-threatening arrhythmias, that is, sustained ventricular tachycardia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The last decade has seen enormous growth in the evidence linking SDB to ventricular arrhythmias, and sudden cardiac death. 12,14,[39][40][41][42][43] Epidemiological data have shown that SDB is associated with a higher burden of complex ventricular ectopy (i.e., bigeminy, trigeminy, and quadrigeminy), non-sustained ventricular tachycardia, and sudden cardiac death. 11 A meta-analysis of 22 studies (42,099 participants) reported that the SDB-related relative risk for sudden death was 1.74 (95% CI: 1.40-2.10).…”
Section: Discussionmentioning
confidence: 99%
“…The last decade has seen enormous growth in the evidence linking SDB to ventricular arrhythmias, and sudden cardiac death. 12,14,[39][40][41][42][43] Epidemiological data have shown that SDB is associated with a higher burden of complex ventricular ectopy (i.e., bigeminy, trigeminy, and quadrigeminy), non-sustained ventricular tachycardia, and sudden cardiac death. 11 A meta-analysis of 22 studies (42,099 participants) reported that the SDB-related relative risk for sudden death was 1.74 (95% CI: 1.40-2.10).…”
Section: Discussionmentioning
confidence: 99%